Teaching practice on the topic of sexuality: a systematic review (Research, Society and Development, 2020)
In the present study, a systematic review was conducted on the topic of sexuality in Brazilian schools, in order to describe the main characteristics of teaching practices in sexual education. The research resulted in seven scientific articles in Portuguese published from 2009 to 2019, obtained from the database of the Periódico Capes. As for the result, four thematic categories emerged for analysis: importance of work; difficulties, methodology adopted and broad themes. Regarding the importance of the sexuality theme, the results of the scientific articles clarify that it is important to work to resolve doubts according to their age groups and for the dissemination of correct information and in a healthy way for life. The difficulties pointed out are related to the lack of theoretical-conceptual preparation on the theme. Regarding the teaching methodology, the articles confirm the trend of lectures, lectures and films. Regarding the topics addressed in the classroom, the investigated articles demonstrate physical and behavioral changes, prevention against STD / AIDS, followed by pregnancy. The results show the presence of work with the theme of sexuality in Brazilian schools, however, there is a need for access to teacher professional development in sex education to provide security and autonomy to teaching work. Also the need for integration with the family and health professionals for the success of sex education in the school context.